2011
DOI: 10.1128/cvi.00296-10
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of IgG-Coated Targets Results in Activation and Secretion of Soluble CD40 Ligand and RANTES by Human Platelets

Abstract: Platelets are crucial elements for maintenance of hemostasis. Other functions attributable to platelets are now being appreciated, such as their role in inflammatory reactions and host defense. Platelets have been reported to bind immunological stimuli like IgG complexes, and for nearly 50 years it has been speculated that platelets may participate in immunological reactions. Platelets have been reported to bind and internalize various substances, similar to other leukocytes, such as macrophages and dendritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…RANTES is stored in platelet a-granule and recruits inflammatory cells to sites of infection. 31,32 It was newly discovered that platelets are a source of MIF, a cytokine with chemokine-like features. 1,29,30 We recently showed that RANTES is secreted from platelets over time upon stimulation in suspension with the oral pathogen P. gingivalis and Pam 3 CSK 4 , showing that the chemokine is secreted from platelets as an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…RANTES is stored in platelet a-granule and recruits inflammatory cells to sites of infection. 31,32 It was newly discovered that platelets are a source of MIF, a cytokine with chemokine-like features. 1,29,30 We recently showed that RANTES is secreted from platelets over time upon stimulation in suspension with the oral pathogen P. gingivalis and Pam 3 CSK 4 , showing that the chemokine is secreted from platelets as an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions require various platelet surface proteins, including toll‐like receptors, fibrinogen receptors, and FcγRIIA (Fitzgerald et al ., ; Blair et al ., ). FcγRIIA is the only IgG receptor present on human platelet surfaces and is responsible for binding and internalization of IgG‐containing targets (King et al ., ; Worth et al ., ; Antczak et al ., ). Specifically, we have recently shown that platelets are capable of binding and internalizing IgG‐coated latex beads, and the internalization is dependent on FcγRIIA and actin polymerization, similar to phagocytosis observed in leukocytes (Antczak et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…For instance, CCL5 can be expressed by platelets, endothelial cells, bronchial epithelial cells, and cells of the immune system (e.g. macrophages, monocytes, natural killer cells, and dendritic cells) [8]. Kruppel-like factor 13 (KLF13) controls the transcription of CCL5 in T lymphocytes [9].…”
Section: Introductionmentioning
confidence: 99%